1990
DOI: 10.1007/bf01409208
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in left ventricular hypertrophy and left ventricular diastolic function following verapamil therapy in mild to moderate hypertension

Abstract: We evaluated the effect of verapamil therapy on left ventricular hypertrophy and left ventricular diastolic function in 13 patients with mild to moderate hypertension. Left ventricular hypertrophy was determined by M-mode echocardiographic measurements of interventricular septal thickness (IVST), posterior wall thickness (PWT) and left ventricular mass index (LVMI) both before (T0) and after 3 months (T3) of verapamil therapy. Left ventricular diastolic transmitral flow was measured by pulsed Doppler indices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…'72 In another 3-month trial with verapamil, significant reductions in LVMI occurred (p<0.05) with preservation of systolic function. 173 Furthermore, diastolic function improved, as assessed by pulsed Doppler velocity profiles of transmitral flow. Longterm verapamil therapy (12 mo) also was associated with a return of diastolic function to normal.174 In this study, Doppler analysis revealed a significant increase in the ratio of ear1y:late diastolic filling velocities at 6 and 12 months after the initiation of verapamil.…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
See 1 more Smart Citation
“…'72 In another 3-month trial with verapamil, significant reductions in LVMI occurred (p<0.05) with preservation of systolic function. 173 Furthermore, diastolic function improved, as assessed by pulsed Doppler velocity profiles of transmitral flow. Longterm verapamil therapy (12 mo) also was associated with a return of diastolic function to normal.174 In this study, Doppler analysis revealed a significant increase in the ratio of ear1y:late diastolic filling velocities at 6 and 12 months after the initiation of verapamil.…”
Section: Calcium Channel Blockersmentioning
confidence: 98%
“…Other 3-month trials found substantial reductions in LV mass with erap pa mil. '^^, 173 In a 12-month open-label trial, LVMI was reduced 15.3% with a single daily verapamil dose of 240 mg.174 Both PWT and LV SWT were also significantly reduced. These changes in LV mass and structure were associated with improvements in LV diastolic filling values.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%